Vicarious Social Defeat Stress Induces Depression-Related Outcomes in Female Mice - Iñiguez, Sergio D.; Flores-Ramirez, Francisco J.; Riggs, Lace M.; Alipio, Jason B.; Garcia-Carachure, Israel; Hernandez, Mirella A.; Sanchez, David O.; Lobo, Mary Kay; Serrano, Peter A.; Braren, Stephen H.; Castillo, Samuel A. (Biological psychiatry (1969), 2018)
Stress is a prevailing risk factor for mood-related illnesses, wherein women represent the majority of those affected by major depression. Despite the growing literature suggesting that affective disorders can arise after a traumatic event is vicariously experienced, this relationship remains understudied in female subjects at the preclinical level. Thus, the objective of the current investigation was to examine whether exposure to emotional and/or psychological stress (ES) mediates depression-related outcomes in female mice. Female C57BL/6 mice (8 weeks old, null parity) vicariously experienced the defeat bout of a male conspecific, by a male CD1 aggressor, for 10 consecutive days. Twenty-four hours after the last stress exposure, female mice were tested in the social interaction, sucrose preference, tail suspension, or elevated plus maze tests. Furthermore, we examined whether ketamine and chlordiazepoxide, pharmacological agents used to treat mood-related disorders in the clinical population, would reverse the ES-induced social dysfunction. When compared with control mice, female mice exposed to ES displayed decreased social behavior and preference for sucrose, along with increased immobility in the tail suspension test. Also, they displayed higher levels of blood serum corticosterone, as well as decreased body weight. Lastly, the ES-induced avoidance-like phenotype was ameliorated by both ketamine and chlordiazepoxide. Our data indicate that female mice exposed to ES display a behavioral and physiologic profile that mimics symptoms of depression in the clinical population. As such, this experimental model may be adopted to examine vicarious stress-induced mood-related disorders, as well as pharmacological antidepressant response, in a sex-specific manner.